Assessing the effects of cascade dams on river ecological status using multi-species interaction-based index of biotic integrity (Mt-IBI). (1st December 2021) - Zhu, Mengjie; Yang, Nan; Li, Yi; Zhang, Wenlong; Wang, Linqiong; Niu, Lihua; Wang, Longfei; Zhang, Huanjun
Abstract: Cascade dams have exerted significant effects on river ecosystems. To quantitatively assess dam-induced effects on river ecological status, a novel multi-species interaction-based index of biotic integrity (Mt-IBI) was developed. Benthic microbiota was selected as a bio-indicator for its sensitivity to the environmental disturbance. An environmental DNA metabarcoding tool was used to identify microbiota (bacteria, protozoan, and metazoan). The Mt-IBI was applied to assess the ecological status of the Hanjiang River, a representative dam-affected river in China. Fifteen sampling sites along the Hanjiang River were sampled in June 2018. Seven core metrics were screened from a total of 364 candidate metrics to calculate the value of the Mt-IBI. The Mt-IBI of the Hanjiang River ranged from 1.90 to 6.39, with a mean value of 4.02. The mean values of Mt-IBI at the reservoir and riverine side of dams were 2.11 and 3.81, respectively. The downstream reach without dam constructions had the highest mean Mt-IBI (5.79). Thus, the continuity of the river was strongly related to the Mt-IBI. Structural equation models (SEMs) were further established to identify the dominant environmental variables in the dam-affected river. The SEMs indicated that flow velocity (coefficient 0.749) was the most important determinant of ecological status in the Hanjiang River. Water organic matter also played a vital role in determining the ecological status of the Hanjiang River, and exerted the strongest direct effect ( P  < 0.001, r = 0.712). The reliability of SEMs was verified by building a support vector regression model (R 2  = 0.8141). This study can provide new tools for ecological assessment and diagnosis, and provide a new perspective for the management of cascade dams. Highlights: A multi-species interaction-based index of biotic integrity was developed. Mt-IBI was applied to quantitatively assess the ecological status of Hanjiang River. Mt-IBI existed an obvious difference between the riverine and reservoir side. SEMs was built and validated to identify the key environmental factors. Flow velocity dominated the river ecosystem mediated through water organics.